Focus Time for Wellbeing and Work Engagement of Information Workers - Saha, Koustuv; Iqbal, Shamsi (CHI EA '23: Extended Abstracts of the 2023 CHI Conference on Human Factors in Computing Systems, 2023)
Having little time for focused work is a major challenge in information work. While research has explored computing-assisted user-facing solutions for protecting time for focused work, there is limited empirical evidence about the effectiveness of these features on wellbeing and work engagement. Towards this problem, we study the effects of automatically scheduling time for focused work on people’s work calendars using the Focus Time feature on Outlook calendars. We conducted an experimental study over six weeks with 15 Treatment and 10 Control participants who responded to survey questions on wellbeing and work engagement throughout the study. We find that the Treatment participants showed higher wellbeing, including increased excitement, relaxation, and satisfaction, and decreased anger, frustration, tiredness, and stress. We study the needs, benefits, and challenges of scheduling focus time, and discuss the importance and design recommendations for enabling mechanisms and tools supporting focused work.